Evaluating possibility of creating modular DC/DC power supplies with configurable structure - V. A. Shpenst; E. A. Orel (Омский научный вестник, 2022)
The paper deals with the problem of creating power supplies for autonomous electrical complexes. The paper demonstrates that the lifetime and efficiency of their operation can be improved by using two fundamental principles: modular construction of the system and intellectual principles of its operation. The article proposes the idea of creating a configurable power supply with power range up to 10 kW, consisting of typical, mass-produced power modules forming together a structure MN, where it is possible to change their interconnections and perform current and voltage control of each module.